Rancang Bangun Sistem Pengabutan Air Untuk Ruangan Kumbung Jamur: Studi Kasus Budidaya Jamur Tiram Di Dusun Mulyosari - Ferdiansyah Hidayatulloh, Muhammad; Arifin, Samsul; Islamiyah, Mufidatul (P3M Politeknik Negeri Banjarmasin, 2022)
This study discusses the general conditions in oyster mushroom cultivation, namely temperature and humidity, these two factors greatly affect the growth and health of oyster mushrooms so that farmers find it difficult to regulate the temperature and humidity of oyster mushroom kumbung to get the right temperature. Mushroom farmers usually do watering manually using an ordinary plant sprayer based on a thermometer. From the information obtained directly from the oyster mushroom farmers, they need a dew spray system in order to keep the kumbung mushroom temperature stable and moist. In this study, it was designed to control temperature and humidity in the kumbung mushroom using a misting system. The tool is a dew water misting system that can work automatically. This system involves a DHT11 temperature sensor as an input for reading the humidity temperature value of the mushroom kumbung which then the humidity temperature value data will be processed by the Wemos D1 R2 microcontroller and then the relay is used to turn on the pump automatically, a 100PSI pressurized water pump is used for output which will push water through PU hose and produce dew mist from the nozzle hole, the fine water spray produced by the nozzle is felt to be more effective in influencing the temperature and humidity in the kumbung mushroom. In this study, it was shown that the water misting system for the mushroom kumbung could affect the growth of fungi, seen in the growth of fungi starting from the emergence of faster growth of pin heads or ovules and also from pin heads to mushrooms blooming 3 days faster than the growth of mushrooms.have to spray it conventionally